2020
DOI: 10.1186/s12941-020-00371-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro estimation of superfluid critical extracts of some plants for their antimicrobial potential, phytochemistry, and GC–MS analyses

Abstract: Background Along with swift economic evolution and continuous amelioration of lifestyle, people at present are paying more attention to health issues. Synthetic drugs will be compensated with other natural ones that belong to natural origin. Plants have always been considered as sources of several compounds that are used in many fields, especially human and animal health, starting from boosting immunity to the treatment of infectious diseases caused by some pathogenic microbes such as bacteria, fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In China, E. coli is the predominant ESBL producer, and the antimicrobial resistance surveillance programme showed that the prevalence of ESBL-producing E. coli increased from 38.9% in 2005 to 55.8% in 2014, while that of K. pneumoniae has declined (decreased from 39.1 to 29.9%), but it is still maintained at a high level [ 23 ]. The high prevalence of ESBL among Enterobacteriaceae mostly due to overuse of antibiotic, non-adjusted course of the drug or uncompleted dosage and inappropriate antibiotic administration [ 24 ]. On the other hand, BLICs and carbapenems are the most common agents used in patients with severe infections caused by ESBLs producers [ 9 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, E. coli is the predominant ESBL producer, and the antimicrobial resistance surveillance programme showed that the prevalence of ESBL-producing E. coli increased from 38.9% in 2005 to 55.8% in 2014, while that of K. pneumoniae has declined (decreased from 39.1 to 29.9%), but it is still maintained at a high level [ 23 ]. The high prevalence of ESBL among Enterobacteriaceae mostly due to overuse of antibiotic, non-adjusted course of the drug or uncompleted dosage and inappropriate antibiotic administration [ 24 ]. On the other hand, BLICs and carbapenems are the most common agents used in patients with severe infections caused by ESBLs producers [ 9 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower layer which contains fatty acids methyl esters (FAMEs) was separated with chloroform, and the final FAMEs product was obtained by evaporating chloroform from the solution. FAMEs were analyzed by GC-MS [37,40].…”
Section: Methyl Ester Preparation and Fatty Acid Analysismentioning
confidence: 99%
“…Second stage includes testing effect of five factors on lipid production to reach optimum conditions of M. racemosus AH1 for lipid production. Table 1 shows different factors and their levels for lipid production, where factors include temperature (15,20,25,30, and 35 °C), initial pH (5, 6, 7, 8, and 9), incubation time (8, 9, 10, 11, and 12 days), different concentrations of soluble starch (10,20,30,40, and 50 gL −1 ), and different concentrations of yeast extract (1, 2, 3, 4, and 5 gL −1 ). Table 2 illustrates L25 array of Taguchi design which contains different factors and their levels to produce high quantities of lipids by M. racemosus AH1.…”
Section: Optimization Of Lipid Production Using a Statistical Designmentioning
confidence: 99%
“…Moreover, the number of multidrug-resistant B. fragilis isolates has increased over the last decade [ 17 19 ]. Improper and excessive use of antibiotics without a doctor’s supervision are the reason for promotes bacterial resistance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%